1978
DOI: 10.1111/j.0954-6820.1978.tb08430.x
|View full text |Cite
|
Sign up to set email alerts
|

Bartter's Syndrome without Hyperplasia of the Juxtaglomerular Apparatus, Treated with Indomethacin

Abstract: ABSTRACT. The present report describes a case of potassium‐wasting nephropathy with the physiological and endocrinological findings that are typical for Bartter's syndrome (BS). However, the renal juxtaglomerular apparatus shawed no hyperplasia at two renal biopsies two years apart. The short‐term (9 days) effect of indomethacin in combination with spironolactone was a suppression of hyperreninemia and hyperaldosteronism and an increase in vascular sensitivity to angiotensin II associated with potassium and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…They also reported that infusion of albumin was associated with a rapid increase in serum potassium and a reduction in aldosterone secretion rate [8]. The work of Kornerup and colleagues suggested that longterm treatment with indomethacin may be ineffective in maintaining normal potassium balance in Bartter syndrome [9]. Konomi, et al, reported the occurrence of pseudotumor cerebri in Bartter syndrome during indomethacin therapy [14].…”
Section: Bartter Syndrome Treatment Research Progressmentioning
confidence: 99%
See 1 more Smart Citation
“…They also reported that infusion of albumin was associated with a rapid increase in serum potassium and a reduction in aldosterone secretion rate [8]. The work of Kornerup and colleagues suggested that longterm treatment with indomethacin may be ineffective in maintaining normal potassium balance in Bartter syndrome [9]. Konomi, et al, reported the occurrence of pseudotumor cerebri in Bartter syndrome during indomethacin therapy [14].…”
Section: Bartter Syndrome Treatment Research Progressmentioning
confidence: 99%
“…The use of indomethacin has been reported by many authors including Verberckmoes, et al, Zancan and colleagues, Littlewood and colleagues, Proesmans and colleagues, Dequiedt, et al, Kornerup and colleagues, Konomi, et al, Valles, et al, Floret, et al, Favre, et al, and Storm and colleagues[1,3,[9][10][11][12][13][14][15][16][17].…”
mentioning
confidence: 99%